Characteristics of graduating US allopathic medical students pursuing a career in neurology. (23rd April 2019) - Gutmann, Laurie; Cahill, Carolyn; Jordan, Justin T.; Gamaldo, Charlene E.; Santini, Veronica; Ali, Imran; Soni, Madhu; Wilson, Rujuta B.; Said, Rana; Czeisler, Barry M.; Smith, A. Gordon
Abstract : Objectives: To identify factors associated with medical students becoming neurologists because, despite the increasing burden of neurologic disorders, there is a growing neurologist shortage. Methods: Deidentified data from the Association of American Medical Colleges Matriculating Student Questionnaire (MSQ) and Graduation Questionnaire (GQ) were obtained for the graduation years 2013 to 2014 through 2016 to 2017. Logistic regression was used to assess demographic characteristics and responses to training and career-related questions in association with specialty choice (intent to enter neurology). Results: Of the 51, 816 students with complete data, 1, 456 (2.8%) indicated an intent to enter a neurology residency. Factors associated with an increased likelihood of entering neurology were a student's rating of excellent for their basic neuroscience course and neurology clerkship, participation in an MD/PhD program, majoring in neuroscience or psychology as an undergraduate, a selection response of "content of the specialty was a strong influence on career choice, " and indicating interest in neurology on the MSQ. Factors associated with a decreased likelihood of entering neurology were a higher-priority response on the GQ for salary, work/life balance, and personal fit of the specialty. Conclusion: Data from surveys at the entry into and graduation from medical school suggest several approaches to increase the number of medical students entering neurology, including a focus on the student-reported quality of the basic neuroscience course and neurology clerkships, targeted engagement with MD/PhD students, and mentoring programs for students interested in neurology. Efforts to improve salaries for neurologists, to reduce medical school debt, and to improve work/life balance may also help to attract more students.